Pergamon, Türkei: Die Arbeiten der Jahre 2012 und 2013 - Pirson, Felix (e-Forschungsberichte des DAI, 2023)
The activities of the Pergamon-excavation in 2013 were part of the continuing research program on the urban organism of the Hellenistic residential city and on Pergamon’s countryside. The program also includes studies of the ancient necropolis and the natural sanctuaries as integral elements within the presentation of suburbs and hinterland. The campaign focused on (1) the inner-city survey at the western slope of the city-hill, (2) the excavation of the alleged rock-cut sanctuary 4 and (3) the street system of the western slope, (4) the excavation of the south-eastern necropolis, (5) the new archaeological and architectural study of the Lower Agora, (6) the investigation of natural sanctuaries in the surroundings of Pergamon and finally (7) the prehistoric survey of the Kaikos valley. The extensive conservation and restoration works will be presented in a separate report.